Tactical Casualty Care and Emergency Evacuation for Health Security Personnel-An Updated Review - AlHajri, Mohammed Ali Masoud; Alnami, Ishaq Jabera,; Ali Saeed Alzahrani,; Hashim Albader Ali Alnemi,; Abdullah Saeed Abdullah Alqahtani,; Aziz Hamad Al Sharaf,; Abdulaziz Habis Aldhafeeri,; Khalid Hathal Mohammad Alotiabi,; Abdullah Mohammed Abdullah Aldawsari,; Mabkhoot Mohammed Mabkhoot Aldawsari,; Faris Salem Bin Mohammed Al Habuban,; Meshari Saud Aldawsari,; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Tactical Emergency Medical Support (TEMS) has emerged as a critical component of modern law enforcement operations, addressing the limitations of conventional emergency medical services (EMS) in hostile, high-risk environments. Derived from military medical practices such as Tactical Combat Casualty Care (TCCC), TEMS emphasizes rapid assessment, lifesaving intervention, and evacuation under active threat conditions. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to provide an updated overview of tactical casualty care and emergency evacuation principles applicable to health security and law enforcement personnel, highlighting operational frameworks, assessment methodologies, and extraction strategies. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative review approach was employed, synthesizing historical development, operational doctrine, and evidence-informed practices related to TEMS. Key concepts analyzed include zones of care (hot, warm, cool), the Rapid and Remote Assessment Methodology (RRAM), the XABCDE primary survey, and tactical extraction and evacuation techniques. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review identifies zone-based care prioritization as central to effective TEMS operations, enabling providers to balance clinical intervention with tactical safety. RRAM supports decision-making by integrating threat assessment and medical urgency, while the XABCDE framework ensures structured identification of life-threatening injuries. Evidence supports rapid hemorrhage control, limited airway intervention under threat, and prompt extraction to safer zones to reduce preventable mortality. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective TEMS relies on the integration of tactical awareness and medical expertise. Structured assessment, disciplined intervention, and coordinated evacuation are essential to optimizing survival while preserving provider safety in hostile environments.